The presence and the content of Monacolins in Red Yeast rice prepared from Thai glutinous rice - Em On Chairote (2018)
Red yeast rice which is a product of solid fermentation was prepared from several kinds of Thai glutinous rice (Oryza sativa L.) cv. Korkor 6 (RD6), Kam (Kam), and Sanpatong1 (SPT1). Monascus purpureus CMU001 isolated from available Chinese red yeast rice was used as the fermentation starter. The analysis for the presence and the content of monacolins, the cholesterol-lowering compounds, were carried out using high performance liquid chromatography (HPLC). The presence of the monacolins was confirmed by the retention time of the reference compounds and LC-MS. The results were compared to those obtained from the Chinese red yeast rice and Thai non-glutinous rice (O. sativa L. cv. Mali105). The chromatograms show the presence of monacolin K acid form (MKA), compactin (P1), monacolin M acid form (MMA), monacolin K (MK), monacolin M (MM), and dehydromonacolin K (DMK). A large peak of a compound with the molecular weight of 358 was also detected but could not be identified. The amount of two important monacolins, compactin, and monacolin K, were determined. It was found that the highest amount of compactin and monacolin K were 21.98 and 33.79 mg/g, respectively, when using Thai rice varity O. sativa L. cv. RD6 which was fermented without adding soybean milk. © 2008 Springer Science+Business Media B.V.